Analisis Kemampuan Siswa dalam Menyelesaikan Persamaan Linear Satu Variabel Pada Siswa Kelas VIIIA SMPK St. Paulus Karuni - Grassiana Misseri Cordia (Journal of Classroom Action Research, 2023)
Based on the test results on the material about linear equations of one variable, students of class VIIIA SMPK St. Paulus Karuni show that students still have difficulty in solving linear equations of one variable. This is because the use of strategies in solving linear equations of one variable is still minimal and the teacher does not emphasize the most important part in solving the problem so that students still make mistakes. During the learning process, students have been taught using the Metacognitive-discursive approach. The Metacognitive approach emphasizes the learning process that requires students to give reasons for each answer, comment on wrong or erroneous answers using axioms and theorems that have been taught. Discursive means that teachers must adopt a teaching culture where before the students answer or comment on the wrong answer, the students first raise their hands and after being given the opportunity, the students can answer or comment. This study aims to determine the extent of students' ability to solve linear equations of one variable (PLSV) by using strategies that have been developed by teachers and researchers in solving PLSV problems. The subjects of this study amounted to 15 people. The results showed that of the 15 students who solved the problem, 13 of them solved correctly by giving reasons for their answers and the other 2 were wrong in calculating the final result. After the students were taught using the strategy developed by the teacher and researcher, there were 3 different variations of answers. Of these three answers, there were 2 types of answers that were solved correctly and one of the answers had a calculation error in the last part. In the first 2 types of answers, there is a difference where one type of answer students calculates to get the final result in the simplest form. This means that students still use additional rules to simplify the term.